Father Anastasius Odaye Dogli (1888–1970) and the Inception of Indigenous Catholic Clergy in Ghana - Mensah, Michael Kodzo (Exchange, 2022)
The historiography of the inception of the Catholic Church in Ghana has focused largely on the activities of the European missionaries. This has left a gap in our knowledge regarding their first indigenous collaborators and their contribution. This is particularly the case of the Rev Fr Anastasius Odaye Dogli (1888–1970), the first indigenous Catholic priest of the Gold Coast about whom only scant literature exists. This article seeks to complement the work of earlier mission historiographers, by retrieving archival material from various sources in Ghana, Togo, and Italy, and sets out to retrieve his narrative blurred by a hundred years of legends that have emerged through oral tradition. It examines the challenges and struggles of a young African who broke through stereotypical, cultural, and colonial barriers to lay the foundations for a centenary of indigenous Roman Catholic clergy in Ghana.